Program Kongsi Rezeki 4.0 helps the students in need - Norhidayah, Mohamad (2018)
Pekan, 14 December – Student Affairs & Alumni Department (SAffAD) continues to organize Program Kongsi Rezeki for the fourth year in a row. It is an initiatives in helping the student by preparing and selling lunch at only RM 1.00.